(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Higher vocational colleges have trained many talents for the society, provided useful talents for all sectors of society, and greatly promoted social development. In order to give full play to its role, higher vocational colleges need to strengthen their own management, of which financial management is the key. Only by ensuring the quality of financial management can they ensure their stable development. However, by observing the current situation of financial management in higher vocational colleges, we can find that there are many problems, which greatly affect the healthy development of higher vocational colleges. Therefore, this paper will first analyze the current situation of financial management in higher vocational colleges, and then elaborate the effective measures to improve financial management in higher vocational colleges from the perspective of internal control, hoping to provide useful reference for the majority of higher vocational colleges.